Characteristics Evolution of Multiscale Structures in Deep Coal under Liquid Nitrogen Freeze-Thaw Cycles. (13th October 2021) - Sun, Yingfeng; Zhao, Yixin; Li, Yulin; Danesh, Nima Noraei; Zhang, Zetian
Abstract : Liquid nitrogen freeze-thaw fracturing has attracted more and more attention in improving the coal reservoir permeability. In order to reveal the impact of liquid nitrogen freeze-thaw on the multiscale structure of deep coal, the multiscale structure evolution law of deep and shallow coal samples from the same seam in the Qinshui coalfield during the liquid nitrogen freeze-thaw cycling was investigated using NMR T 2 spectrum, NMRI, and SEM. The connectivity between mesopores and macropores in deep and shallow coal is improved after liquid nitrogen freeze-thaw cycles. The influence of liquid nitrogen freeze-thaw cycles on the structure evolution of deep and shallow coal is the formation and expansion of microscopic fractures. The initial NMR porosity of deep coal is lower than that of shallow coal from the same coalfield and coal seam. The NMR porosity of both the deep and shallow coal samples increases with the increase of the number of freeze-thaw cycles, and the NMR porosity growth rate of the deep sample is lower than that of the shallow sample.